Islamic Law Thought - T. Wildan T. Wildan (Hukum Keluarga Islam IAIN LANGSA, 2022)
This study aims to describe the views of the Syafi'iyah clerics on the concept of kafāah; this is important to discuss because so far, in the opinion of the general public and especially Aceh, kafāah is only limited to equivalence in the field of religion. In contrast, in other fields, its existence is ignored. This research methodology uses normative juridical with a literature review; then, the descriptive analysis is used to describe the collected data that has been reduced; the primary data in this study are the works of Syafi'iyyah scholars. As for the findings of the study; the conception of kafāah in Acehnese society only focuses on conformity in terms of religion because this is the most basic right of a marriage, without having to fulfil other fields of kafāah, while in the view of Syafi'iyah scholars, religion is the main requirement of kafāah, but other aspects of kafāah must also be considered and are as important as the religious side, such as; heredity, occupation and no defects experienced by the prospective husband which can occur faskh, and all the standardization of kafaah become a condition for the validity of the marriage under certain conditions